2022
DOI: 10.1177/10225536221122340
|View full text |Cite
|
Sign up to set email alerts
|

Risk of reoperation after primary anterior cruciate ligament reconstruction in children and adolescents

Abstract: Objective To examine the incidence and risk factors of any-cause reoperation after primary ACLR in children and adolescents. Design Retrospective Cohort Setting Electronic medical records from a large tertiary care, single institution integrated healthcare delivery system. Patients Patients were under the age of 18 years and had anterior cruciate ligament reconstruction. They were excluded if they had a multi-ligamentous knee injury or <1 year follow-up. Interventions Patients were further identified to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this study, there was a 16% rate of all‐cause reoperation after ACLR. There are varying percentages available in the current literature; however, 16% is likely less than the reported average [20, 33, 44]. Van Dijck et al reported a reoperation rate of 27.6% with an average follow‐up of 7.4 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, there was a 16% rate of all‐cause reoperation after ACLR. There are varying percentages available in the current literature; however, 16% is likely less than the reported average [20, 33, 44]. Van Dijck et al reported a reoperation rate of 27.6% with an average follow‐up of 7.4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although meniscal repair is generally a successful procedure, as studies continue to show improved survival of cartilage, and slower progression to end stage degenerative joint disease after meniscal repair, surgeons must be conscious of the risk of reoperation associated with concomitant meniscal repair and ACLR [45]. Similarly, although hamstring autografts help to prevent the risk of anterior knee pain in our younger patients, they have shown higher graft failure rates after ACLR [12], especially in younger patients who are already at risk for reoperation [18, 33]. Interestingly, there is minimal data in the current literature for the most prominent feature of our model: diagnosis of systemic inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation